(untitled) - Thais Jerez Jaime; Tatiana Jerez Jaime; Patrícia Ormiga; Fabiano Leal; Osvania Maris Nogueira; Nilton Rodrigues (Sociedade Brasileira de Dermatologia, 2013)
Cutaneous endometriosis is a rare manifestation of endometriosis, representing 0.5% to 1% of all endometriosis cases. It can be divided into primary and secondary, when appearing spontaneously or after a surgical procedure, when it is mostly found on surgical scar tissue. Some etiologies were proposed, but none of them could entirely explain the appearance of the tumor. Differential diagnosis includes melanoma, metastatic nodule, keloid and pyogenic granuloma. Dermoscopic features are not yet well established, but there are some characteristics that suggest the diagnosis. Treatment is surgical in larger sized lesions. Malignization can occur. The screening for endometriosis is mandatory by means of gynecologic, imaging and marked-tumor evaluation. We report a case of primary umbilical endometriosis and discuss its dermoscopic aspects. A endometriose cutânea é forma rara de endometriose, representando de 0,5% a 1% de todos os casos da doença. Pode ser dividida em forma primária, de surgimento espontâneo, ou secundária, após procedimentos cirúrgicos aonde geralmente encontra-se sobre a cicatriz cirúrgica. Diversas etiologias foram propostas, porém, nenhuma capaz de explicar inteiramente seu aparecimento. Diagnósticos diferenciais incluem melanoma, nódulos metastáticos, quelóide e granuloma piogênico. A dermatoscopia da lesão ainda não foi bem estabelecida, mas existem alguns achados que podem sugerir o diagnóstico. O tratamento é cirúrgico nos casos de lesões maiores e o screening para endometriose é mandatório através de avaliação ginecológica, de imagem e marcador tumoral. Relatamos um caso de endometriose cutânea primária e discutimos seus aspectos dermatoscópicos.